Specialist and family physician collaboration: Insights from primary care‐based memory clinics. (11th April 2019) - Lee, Linda; Hillier, Loretta M.; Locklin, Jason; Lumley‐Leger, Kelly; Molnar, Frank
Abstract: Given limited available geriatric specialists and complexity of dementia care, there is a need for greater collaboration between primary care and specialists to better meet the needs of persons with dementia. Meaningful family physician—specialist collaboration has the potential to improve health outcomes, timely access to care and more appropriate healthcare resource utilisation. Primary Care Collaborative Memory Clinics (PCCMCs), which include specialist support, provide a significant opportunity for studying the family physician–specialist interface. This study aimed to explore the nature of collaborative relationships between memory clinic family physicians and specialists caring for persons with memory concerns in PCCMCs across Ontario, Canada. Family physicians ( N = 71) attending an education session and specialists ( N = 21) completed a survey in the fall of 2017 that measured frequency and amount of collaboration, perceptions of their relationship and identified factors that enable and challenge collaboration. Descriptive statistics were generated for quantitative data and themes for responses to open‐ended questions were explored using descriptive qualitative content analysis. Specialists and memory clinic family physicians valued their collaboration particularly as related to capacity building for dementia care and desired more time devoted to collaboration. Identified enablers and barriers to collaboration have implications for further integration of specialist support to potentially support improved patient care and further build capacity in primary care to manage dementia care. Opportunities exist for expanding and more intentionally supporting how family physicians and specialists interact with the creation of more formalised processes to support optimal collaboration, including a clear delineation of roles, responsibilities and expectations, more formally planned and structured relationship building and monitoring, identifying and addressing unique barriers to collaboration and use of a variety of methods of communication. Study findings have implications for how specialists and family physicians communicate and collaborate in other programmes for complex chronic conditions.